3) Consider the quadratic \( f(x)=-2 x^{2}-4 x+5 \). \( \begin{array}{ll}\text { a. What is the average rate of change over } & \text { b. What is the average rate of change over } \\ \text { the interval from } x=0 \text { to } x=2 \text { ? } & \text { the interval from }-7 \leq x \leq-4 ?\end{array} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To find the average rate of change of the function \( f(x) = -2x^2 - 4x + 5 \) over an interval, we use the formula: \[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \] **For part a**, over the interval from \( x = 0 \) to \( x = 2 \): First, calculate \( f(0) \) and \( f(2) \): \[ f(0) = -2(0)^2 - 4(0) + 5 = 5 \] \[ f(2) = -2(2)^2 - 4(2) + 5 = -8 - 8 + 5 = -11 \] Then plug these values into the average rate of change formula: \[ \text{Average Rate of Change} = \frac{f(2) - f(0)}{2 - 0} = \frac{-11 - 5}{2 - 0} = \frac{-16}{2} = -8 \] The average rate of change over the interval from \( x = 0 \) to \( x = 2 \) is \(-8\). **For part b**, over the interval from \( -7 \) to \( -4 \): Calculate \( f(-7) \) and \( f(-4) \): \[ f(-7) = -2(-7)^2 - 4(-7) + 5 = -2(49) + 28 + 5 = -98 + 28 + 5 = -65 \] \[ f(-4) = -2(-4)^2 - 4(-4) + 5 = -2(16) + 16 + 5 = -32 + 16 + 5 = -11 \] Now, apply the average rate of change formula: \[ \text{Average Rate of Change} = \frac{f(-4) - f(-7)}{-4 - (-7)} = \frac{-11 - (-65)}{-4 + 7} = \frac{-11 + 65}{3} = \frac{54}{3} = 18 \] The average rate of change over the interval from \( -7 \) to \( -4 \) is \( 18 \).